PENGARUH PENGELOLAAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN UPTD PANTAI PASIR KENCANA KOTA PEKALONGAN - Anwarudin, Panut (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
The purpose of this research is to determine the influence of knowledge, skills and attitudes on employee performance at UPTD Pasir Kencana Beach, Pekalongan City, and to analyze whether knowledge, skills and attitudes together influence employee performance at UPTD Pasir Kencana Beach, Pekalongan City. This research uses questionnaire data or is carried out by distributing questionnaires to the parties who are respondents in this research. Meanwhile, data analysis techniques are instrument quality testing, multiple linear regression analysis, and hypothesis testing. The research results found that knowledge had a positive and significant effect on employee performance at UPTD Pasir Kencana Beach, Pekalongan City. Suitability of skills has an effect but is not significant on employee performance at UPTD Pasir Kencana Beach, Pekalongan City. Meanwhile, attitude suitability has a positive and significant effect on employees at UPTD Pasir Kencana Beach, Pekalongan City, seen from the results of the beta value analysis of the most dominant variable on employee performance at UPTD Pasir Kencana Beach, Pekalongan City, is attitude suitability